Therapeutic activity of high-dose intratumoral IFN-β requires direct effect on the tumor vasculature - Spaapen, Robbert (2014)
Endogenous type I IFN production after innate immune recognition of tumor cells is critical for generating natural adaptive immune responses against tumors in vivo. We recently have reported that targeting low doses of IFN-β to the tumor microenvironment using tumor-specific mAbs can facilitate antitumor immunity, which could be augmented further with PD-L1/PD-1 blockade. However, sustained high doses of type I IFNs in the tumor microenvironment, which are potently therapeutic alone, may function through distinct mechanisms. In the current report, we demonstrate that high-dose intratumoral type I IFNs indeed exerted a profound therapeutic effect in the murine B16 model, which unexpectedly did not increase T cell responses. Moreover, bone marrow chimeras revealed a role for type I IFN signaling on nonhematopoietic cells, and most of the therapeutic effect was retained in mice deficient in T, B, and NK cells. Rather, the tumor vasculature was ablated with high-dose intratumoral IFN-β, and conditional deletion of IFN-α/βR in Tie2-positive vascular endothelial cells eliminated most of the antitumor activity. Therefore, the major component of the antitumor activity of sustained high doses of type I IFNs occurs through a direct antiangiogenic effect. Our data help resolve conditions under which distinct antitumor mechanisms of type I IFNs are operational in vivo.